Respuesta :
Answer:
[tex]g_{r}(\sqrt{2},\frac{\pi}{4})=\frac{\sqrt{2}}{2}\\[/tex]
Step-by-step explanation:
First, notice that:
[tex]g(\sqrt{2},\frac{\pi}{4})=f(\sqrt{2}cos(\frac{\pi}{4}),\sqrt{2}sin(\frac{\pi}{4}))\\[/tex]
[tex]g(\sqrt{2},\frac{\pi}{4})=f(\sqrt{2}(\frac{1}{\sqrt{2}}),\sqrt{2}(\frac{1}{\sqrt{2}}))\\[/tex]
[tex]g(\sqrt{2},\frac{\pi}{4})=f(1,1)\\[/tex]
We proceed to use the chain rule to find [tex]g_{r}(\sqrt{2},\frac{\pi}{4})[/tex] using the fact that [tex]X(r,\theta)=rcos(\theta)\ and\ Y(r,\theta)=rsin(\theta)[/tex] to find their derivatives:
[tex]g_{r}(r,\theta)=f_{r}(rcos(\theta),rsin(\theta))=f_{x}( rcos(\theta),rsin(\theta))\frac{\delta x}{\delta r}(r,\theta)+f_{y}(rcos(\theta),rsin(\theta))\frac{\delta y}{\delta r}(r,\theta)\\[/tex]
Because we know [tex]X(r,\theta)=rcos(\theta)\ and\ Y(r,\theta)=rsin(\theta)[/tex] then:
[tex]\frac{\delta x}{\delta r}=cos(\theta)\ and\ \frac{\delta y}{\delta r}=sin(\theta)[/tex]
We substitute in what we had:
[tex]g_{r}(r,\theta)=f_{x}( rcos(\theta),rsin(\theta))cos(\theta)+f_{y}(rcos(\theta),rsin(\theta))sin(\theta)[/tex]
Now we put in the values [tex]r=\sqrt{2}\ and\ \theta=\frac{\pi}{4}[/tex] in the formula:
[tex]g_{r}(\sqrt{2},\frac{\pi}{4})=f_{r}(1,1)=f_{x}(1,1)cos(\frac{\pi}{4})+f_{y}(1,1)sin(\frac{\pi}{4})[/tex]
Because of what we supposed:
[tex]g_{r}(\sqrt{2},\frac{\pi}{4})=f_{r}(1,1)=-2cos(\frac{\pi}{4})+3sin(\frac{\pi}{4})[/tex]
And we operate to discover that:
[tex]g_{r}(\sqrt{2},\frac{\pi}{4})=-2\frac{\sqrt{2}}{2}+3\frac{\sqrt{2}}{2}[/tex]
[tex]g_{r}(\sqrt{2},\frac{\pi}{4})=\frac{\sqrt{2}}{2}[/tex]
and this will be our answer